2024
DOI: 10.1007/s10098-023-02702-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a rubber wood fly ash-based geopolymer for stabilizing marginal lateritic soil as green subbase materials

Wisitsak Tabyang,
Tavorn Kuasakul,
Pongsak Sookmanee
et al.

Abstract: Rubber wood fly ash (RWFA) is one of the main components of biomass ash materials. This research investigates the possibility of using RWFA geopolymer (RWFAG) to stabilize marginal lateritic soil (MLS) as green subbase materials. RWFA was used as a starting material.The studied influence factors included MLS:RWFA ratio, sodium silicate (NS):sodium hydroxide (NH) ratio, soaked and unsoaked conditions, and curing time. The study involved testing the unconfined compressive strength (UCS), indirect tensile strengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…On the one hand, a large number of hydration products covers the surface of the stabilized material to form a solid matrix, which also makes the loose particles interconnected and aggregated into one, so that the mixture forms strength. On the other hand, the hydration products generated by the geopolymer raw materials after alkali excitation effectively fill the pores and other structures inside the stabilized material, which enhances the compactness of the stabilized material and makes the mixture form strength [5,8,12,15]. In addition, it is worth noting that the dosage of geopolymer generally has an optimal value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, a large number of hydration products covers the surface of the stabilized material to form a solid matrix, which also makes the loose particles interconnected and aggregated into one, so that the mixture forms strength. On the other hand, the hydration products generated by the geopolymer raw materials after alkali excitation effectively fill the pores and other structures inside the stabilized material, which enhances the compactness of the stabilized material and makes the mixture form strength [5,8,12,15]. In addition, it is worth noting that the dosage of geopolymer generally has an optimal value.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the geopolymer significantly reduced the leaching of harmful heavy metals. Tabyang W et al [12] used rubberwood fly ash to prepare a geopolymer for the preparation of geopolymer-stabilized marginal laterite subgrade material and tested its mechanical properties. The results showed that the UCS and ITS (indirect tensile strength) of this base material were optimized when the dosage of the geopolymer was 30% and the ratio of sodium silicate to sodium hydroxide was 7:3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation